PERAN GURU PAI DALAM BIMBINGAN DAN KONSELING TERHADAP PEMBENTUKAN AKHLAK SISWA DI SEKOLAH DASAR - Siska Aprilia; Aida Hayani (university Of islam, 2023)
The character of elementary school students is part of the process of shaping their character that can influence how they behave and communicate with others. A guidance and counseling service can assist a teacher of Islamic Studies to provide teachings in guidance and counseling that are aligned with the teachings of Islam in shaping the character of students. The researcher uses a qualitative descriptive research type. Using a literature approach, the method in this research is descriptive analysis analyzed from various scientific literature. The result of this study is to correlate between general guidance and counseling services using the guidance and counseling services according to Imam Al-Ghazali. And the result can influence its success in shaping the character of students to be achieved through an effective and quality process.